PENGARUH PROFITABILITAS, LIKUIDITAS DAN LEVERAGE TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN YANG TERDAFTAR DI INDEKS LQ45 BEI - Merline Julianti,; Ari Sunardi,; Putu Rani Susanthi, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2021)
This research aims to determine the impact of profitability, liquidity and leverage on the dividend policy of companies listed in the Index LQ45 Indonesia Stock Exchange. The samples used in this research are listed in the Index LQ45 Indonesia Stock Exchange which pays dividends 4 consecutive years and which use Rupiah currency. The data analysis method that used in this research was a method of multiple linear regression analysis. This research was conducted with a total of 16 samples of companies listed in the Index LQ45 Indonesia Stock Exchange from period 2016 to 2019.Data testing results find a partial that profitability has significant effect on the dividend policy, while liquidity and leverage have no effect on the dividend policy. The results of simultaneous data testing concluded that profitability, liquidity and leverage simultaneously has significant effect on the dividend policy